2006
DOI: 10.1097/01.bsd.0000190560.20872.a7
|View full text |Cite
|
Sign up to set email alerts
|

Are Drains Useful for Lumbar Disc Surgery?

Abstract: Occurrence of hematoma in the epidural space is common after lumbar disc surgery even if meticulous hemostasis has been achieved. Insertion of a drain decreases both the incidence and the size of hematoma on the first postoperative day as detected by MRI. This may have practical implications for the prevention of significant postoperative fibrosis and obtaining better surgical outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(68 citation statements)
references
References 21 publications
(14 reference statements)
2
66
0
Order By: Relevance
“…Suction drainage can be expected to help obviate the complication in case of certain amount of intraoperative bleeding; however, a multitude of previous studies have shown that it is not a fail-safe way to prevent the catastrophic complication 3456789101112). There was only one prospective study that demonstrated the efficacy of suction drainage in reduction of remaining epidural hematoma 13). Therefore, we conjectured there must be some factors that hamper appropriate function of suction drains, which should also be recognized as the risk factors for POSEH.…”
Section: Discussionmentioning
confidence: 99%
“…Suction drainage can be expected to help obviate the complication in case of certain amount of intraoperative bleeding; however, a multitude of previous studies have shown that it is not a fail-safe way to prevent the catastrophic complication 3456789101112). There was only one prospective study that demonstrated the efficacy of suction drainage in reduction of remaining epidural hematoma 13). Therefore, we conjectured there must be some factors that hamper appropriate function of suction drains, which should also be recognized as the risk factors for POSEH.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative epidural hematomas (EH) have been reported as “very frequent” when radiologic investigation of the postoperative lumbar spine is performed [1]. Postoperative lumbar epidural fibrosis (EF) is the formation of scar tissue over the dura mater following EH [123456789].…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative lumbar epidural fibrosis (EF) is the formation of scar tissue over the dura mater following EH [123456789]. EHs on the first postoperative day of lumbar disc surgery were reported to occur as frequently as 86% after using magnetic resonance imaging (MRI) [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations